Возможность использования гематологического метода для определения жизнеспособности американской белой бабочки (Hyphantria cunea D г.) - Зелинская, Л.M. (Вестник зоологии, 1973)
The data are presented on qualitative and quantitative composition of hemolymph in sound caterpillars, pupae and imago of Hyphantria cunea D r. in individuals affected simultaneously with nuclear polyhedrosis and granulosis and in individuals weakened as a result of starvation or nutrition with unfavourable fodder. A conclusion is made that the hematological method permits predicting viability of the Hyphantria cunea D r. given generation and its progeny.